DEVELOPMENT OF E-BOOKLET BASED ON PROBLEM BASED LEARNING ON ACID BASE MATERIAL FOR PROBLEM SOLVING ABILITY - Burhanudin Milama; Safina Adiliyah; Dila Fairusi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
Teaching materials are a source of learning for students. For this reason, efforts are needed to develop teaching materials that accommodate the needs of students in terms of ease of access, attractive presentation, and encouraging student activity. This research focuses on the development of electronic booklets (e-booklets) using the